The role of high-tech parks in China´s regional economy: empirical evidence from the IC industry in the Zhangjiang High-tech Park, Shanghai - Zeng, Gang; Liefner, Ingo; Si, Yeufang (ERDKUNDE, 2011)
Numerous empirical investigations have been carried out which assess the roles of high-tech parks worldwide. Most of them focus on collaboration within the parks, innovation, and the formation of innovative local clusters, reflecting the perspective of industrialized countries. Chinese high-tech parks, however, are different in many ways. Besides the usual functions of stimulating collaboration and innovation, they are designed to attract foreign investment and to function as hubs for integrated regional economic development. This paper takes one of the country’s leading high-tech parks, Zhangjiang High-tech Park in Shanghai (ZJ), and its most prominent industry, the IC industry (integrated circuits; micro-electronics), as an example. Using survey data from 2008, it analyzes to what extent high-tech parks fulfill their different roles. It turns out that ZJ has successfully attracted FDI, today showing clear signs of technical dependence on foreign companies, at least in the field of advanced machinery. However, as ZJ remains focused on the design, manufacturing and testing of ICs that do not belong to the latest generation, the park has not succeeded in stimulating innovation, with the FDI-focused development policy thus not being successful in this respect. However, ZJ helps to raise the overall technological level in the Yangtze River Delta. The park succeeds in integrating the regional activities into global value chains and acts as an integrated economic hub that combines production factors from Shanghai and other parts of China.